Interannual Abundance Fluctuations of Two Oceanic Squids in the Pacific Ocean Can Be Evaluated Through Their Habitat Temperature Variabilities - Chen, Peng; Chen, Xinjun; Yu, Wei; Lin, Dongming (Frontiers in Marine Science, 2021)
Neon flying squid (Ommastrephes bartramii) and jumbo flying squid (Dosidicus gigas) are two commercially essential oceanic squids in the Pacific Ocean. An in-depth understanding of the mechanisms of their annual and interannual abundance fluctuations under environmental and climate variabilities can ensure ration and suitable management. Thus, the annual and interannual abundance fluctuations of the stock of the western winter-spring cohort of O. bartramii and D. gigas off Peru Exclusive Economic Zone (PEEZ) waters and their association with habitat temperature variabilities are explored in this study based on the historical Chinese Squid-jigging fishery data from 2003 to 2020. The habitat temperature variabilities were defined as the effective principal components of the SST at the squids’ two important habitats (spawning and feeding ground) through life histories according to the principal component analysis. The Hodrick—Prescott filter analysis was conducted to quantify the annual and interannual fluctuations of abundance and habitat temperature variabilities. Furthermore, the generalized additive model (GAM) was employed to investigate their associations. The results demonstrated different but not synchronous trends of abundance for O. bartramii and D. gigas. Regarding O. bartramii, the interannual abundance first decreased (2003∼2013) and then increased (after 2014). For D. gigas, the interannual abundance kept decreasing within 2003∼2020. Their annual trends have presented large fluctuations over years. The results of GAM indicated that using habitat temperature variabilities only can trace the abundance trend of O. bartramii and D. gigas at an interannual but not annual scale. Further studies verified that Pacific Decadal Oscillation (PDO) is a crucial factor affecting the interannual abundance trend of these two squids through the habitat temperature variabilities. However, this study indicates that the habitat temperature variabilities not only are related to other large-scale factors, which are not investigated currently at an interannual scale, but also, are combined with other small- or middle-scale factors at an annual scale on their impacts to the abundance fluctuations of these two squids. Therefore, in order to better explain the mechanisms of annual and interannual abundance fluctuations of O. bartramii and D. gigas under environmental and climate variabilities, the importance of combining other potential factors into consideration is highlighted.